x/3 - 1 + 3/4 = x/2 - 1/4
Soluções para a tarefa
Respondido por
1
Explicação passo-a-passo:
x/3 - 1 + 3/4 = x/2 - 1/4
x/3-x/2=-1/4-3/4+1
x/3-x/2=-0,25-0,75+1
x/3-x/2=-1+1
x/3-x/2=0
x/3=x/2
3x=2x
3x-2x=0
1x=0
x=0/1
x=0
Vamos verificar :
x/3 - 1 + 3/4 = x/2 - 1/4
0/3-1+3/4=0/2-1/4
0-1+3/4=0-1/4
-1+3/4=-1/4
-1/4=-1/4
ok!
Espero ter ajudado!
Perguntas interessantes
Matemática,
10 meses atrás
Português,
10 meses atrás
Português,
10 meses atrás
História,
1 ano atrás
Matemática,
1 ano atrás
Ed. Física,
1 ano atrás
Física,
1 ano atrás
ENEM,
1 ano atrás